Analisis Human Error terhadap penggunaan Peralatan Komunikasi dan Navigasi Kapal Sebagai Penyebab Kecelakaan Kerja - Anak Agung Istri Sri Wahyuni; Dian Wahdiana; Sereati Hasugian; Anak Agung Istri Sinta Bela Paramitha (Jurnal Infokes, 2021)
Human error has long been considered the leading cause of incidents in the shipping sector. It is estimated that between 75% and 96% of marine accidents are caused by human error. Such incidents are also ranked as the leading cause of liability loss, driven by the high costs that can be attributed to the impact of a major event. Human error or human error still often occurs in ship control. The possibility of human error occurring on board is due to the high workload and the influence of an uncomfortable work environment. The purpose of this study was to analyze human error on navigation communication equipment on ships as a cause of accidents in the Bali Strait. This research is a qualitative descriptive study, the data collection technique used is observation, and literature, the data analysis technique used is the qualitative analysis technique. Based on the explanation above, Human error factors in the form of fatigue, stress levels and physical stress that affect concentration are believed to affect safety in the workplace.Meanwhile, decision errors, skill-based errors, perceptions and violations are also categorized as human errors which also contribute to work accidents that result in ship wreck.